Kvinnorshälsaifokus förframtidenssjukvård: Användarcentreradutformning avdigifysiskvårdriktadtillkvinno - Bökmark, Lina; Högberg, Nea; Jönsson, Tilda; Kalm, Sally; Stenlund, Jonna; Wernholm, Matilda N (My University, 2023)
The digitalisation of the Swedish healthcare system has led to increased access to healthcare, despite this the need for specialized healthcare for women remains. This project analyze the user’s needs and requirements on a digiphysical healthcare app designed for women’s health issues with a main focus on contraceptive counseling. This is, for many women, their first introduction to women’s healthcare. Therefore a user centered approach is needed and five different personas were made to be able to adapt the end result for different types of patient journeys. During the project four main factors to a user's experience of women’s healthcare were discovered: availability, approach, trust and communication. The project was executed with an external client, Femcare, with the deliverables questionnaire which consisted of triage questions, anamnesis questions and follow-up questions and also an interface of their healthcare app. The project has been executed according to agile methodologies and in interaction with the users through continuous communication through interviews, usability tests, focus groups and surveys to ensure that the target group’s needs and requirements are met. Important aspects during the formulation of the questionnaire were that the language had to be transparent and inclusive to create trust and contribute to good communication with the caregiver. The user places further requirements on the app’s interface to be seen as professional, modern, discreet and intriguing to encourage use and make it easy to seek care. The results can be used as a foundation by Femcare during the development of their healthcare app.